2014
DOI: 10.3746/jkfn.2014.43.8.1296
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling of Bacillus cereus on Carrot Treated with Slightly Acidic Electrolyzed Water and Ultrasonication at Various Storage Temperatures

Abstract: This study was conducted to develop predictive models for the growth of Bacillus cereus on carrot treated with slightly acidic electrolyzed water (SAcEW) and ultrasonication (US) at different storage temperatures. In addition, the inactivation of B. cereus by US with SAcEW was investigated. US treatment with a frequency of 40 kHz and an acoustic energy density of 400 W/L at 40°C for 3 min showed the maximum reduction of 2.87 log CFU/g B. cereus on carrot, while combined treatment of US (400 W/L, 40°C, 3 min) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Microbial reduction effects of combined treatments were not significantly different regardless of temperature or volume of washing solution ( p < 0.05) ( Table 2 ). Previous studies have reported that higher temperature of treatment solution (25~60 °C) is more effective for reducing pathogenic bacteria in fresh-cut carrot, potato, and bell pepper [ 21 , 29 , 30 ]. However, potatoes washed at 60 °C with US treatment have shown color changes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microbial reduction effects of combined treatments were not significantly different regardless of temperature or volume of washing solution ( p < 0.05) ( Table 2 ). Previous studies have reported that higher temperature of treatment solution (25~60 °C) is more effective for reducing pathogenic bacteria in fresh-cut carrot, potato, and bell pepper [ 21 , 29 , 30 ]. However, potatoes washed at 60 °C with US treatment have shown color changes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Jin, Kim, Ding, & Oh, 2009; Ugarte‐Romero, Feng, & Martin, 2007; Zhou, Feng, & Luo, 2009). However, UW are usually combined with many other technologies such as chemical and physical processing, as it is limited to the extinction of microorganisms when used alone (Chung, Ko, & Shin, 2015; Kim & Oh, 2014; Park et al, 2016; Park, Song, & Ha, 2014). The combined treatment technology (hurdle technology) can be applied sequentially to the properties of the hurdle factors by using a combination technologies to maximize the sterilization and storage effects (Ding, Rahman, Purev, & Oh, 2010; Huang et al, 2006; Rahman, Ding, & Oh, 2010).…”
Section: Introductionmentioning
confidence: 99%